An analysis on finding the optimum die angle of polylactic acid in fused deposition modelling - Sukindar, Nor Aiman; Mohd Ariffin, Mohd Khairol Anuar (Trans Tech Publication, 2016)
Rapid prototyping (RP) has been known as one of the advanced technology that grows tremendously over the few years. Fused Deposition Modeling (FDM) is one of the RP technologies, which is commonly used in producing three dimensional products. The study focus on the effect of dies angle in FDM nozzle and finds the optimum angle know as natural convergent angle (2θo). Polylactic acid (PLA) has been chosen as the material due to lots of advantages including biodegradability and acts as the base material for reconstructive structure for bone material. Extruding PLA material effectively is utilized under simulation method and the data obtain has been recorded. Die angle has been varied from 80o until 160o and it shows a different effect in pressure drop. Pressure drop need to be observed as it affects the road width of scaffold design, thus affecting the quality of the extruded part. The natural convergence angle (2θo) should be closed as to the die angle (2α) in order to get stability and consistency scaffold design. The natural convergent angle is found at 130o and can be considered as optimum die angle.